2010
DOI: 10.4317/medoral.15.e906
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic factors that cause the presence of pain muscle in students of dentistry

Abstract: Objective: To identify the ergonomic factors and the presence of muscular pain in dental students of VIII, IX, X semesters presently practicing at the clinics of the College of Dentistry of university of Cartagena, Colombia, South America. Materials and methods: This is a descriptive study carried out in dental students of the VIII, IX, and X semesters which were undergoing clinical practice at the College of Dentistry of University of Cartagena. A convenience sample of 83 students who met the inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
87
1
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 18 publications
(20 reference statements)
14
87
1
12
Order By: Relevance
“…403 of the students (77.5%) stated that desks and chairs in the classrooms were not comfortable and most (93.5%) had low back pain (p<0.01). These results of our study support the literature demonstrating that low back pain is resulted from staying in sitting position for a long time (7)(8)(9)(10). On the other hand, in another study, it was reported that sitting position was not a risk factor for back pain anymore (5).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…403 of the students (77.5%) stated that desks and chairs in the classrooms were not comfortable and most (93.5%) had low back pain (p<0.01). These results of our study support the literature demonstrating that low back pain is resulted from staying in sitting position for a long time (7)(8)(9)(10). On the other hand, in another study, it was reported that sitting position was not a risk factor for back pain anymore (5).…”
Section: Discussionsupporting
confidence: 82%
“…Students' anthropometric features, gender, smoking habit, time spent on computer, school furniture, and ergonomic problems, including sitting position, are the risk factors for the occurrence of low back pain (2,(6)(7)(8). Sitting for prolonged periods is important for the onset of low back pain (9,10). Ayanniyi et al (11) emphasized that the most important cause of low back pain among adolescents was being in a sitting position for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…The most common site of muscular pain was in the back, neck, shoulders and hands. 10 Sharma P and Golcha V (2011) carried out a study among Indian dentists and found out that there was high prevalence of pain in Indian dentists.…”
Section: 5005/jp-journals-10031-1004mentioning
confidence: 99%
“…Las zonas del cuerpo con mayor reporte de molestias en nuestra investigación resultaron también similares a todos los estudios de prevalencia citados (Rising et al;Tezel et al, 2005;Thorton et al, 2008;Melis et al, 2008;de Carvalho et al;Hayes et al, 2009b;Diaz-Caballero et al). Rising et al, reportó significativamente mayor dolor en espalda media en los hombres (p=0,015) y mayor dolor en cuello y hombro en las mujeres (p=0,004), mismos reportes que presentó nuestro estudio.…”
Section: Discussionunclassified
“…Rising et al (2005), reportaron una prevalencia de un 56-71% de dolor corporal en estudiantes de odontología, distin-guiendo las zonas más afectadas. Diaz-Caballero et al (2010), reportó una prevalencia de dolor muscular de un 80% en estudiantes de odontología, donde también evaluó los factores ergonómicos que causan el dolor muscular.…”
Section: Introductionunclassified